Legal Review of the Implementation of the 2024 Kunti Village Budget Based on the Village Law - Andrik Eko Santoso; Suryadi .; Maria Yosepin Endah Listyowati (UNTAG Law Review, 2026)
This research aims to analyze the implementation of the Village Revenue and Expenditure Budget (APBDes) of Kunti Village for the year 2024 from the perspective of Law No. 6 of 2014 on Villages. The study focuses on two primary aspects: (1) the conformity of village budget planning with statutory regulations, and (2) the conformity of budget implementation in its on-the-ground execution. This study constitutes empirical juridical legal research that integrates a normative approach (statute approach) with a sociological approach to examine the extent to which village financial management regulations are implemented by the Kunti Village Government. Primary data were obtained through interviews with village officials, the Village Consultative Body (BPD), and community members, while secondary data were sourced from statutory documents, APBDes records, and related literature. This study constitutes empirical juridical legal research that integrates a normative approach (statute approach) with a sociological approach to examine the extent to which village financial management regulations are implemented by the Kunti Village Government. Primary data were obtained through interviews with village officials, the Village Consultative Body (BPD), and community members, while secondary data were sourced from statutory documents, APBDes records, and related literature. Based on these findings, this research concludes that the implementation of the APBDes of Kunti Village for 2024 has not fully adhered to the principles of transparency, accountability, participation, and legal compliance as mandated by Law No. 6 of 2014. Recommendations include enhancing the capacity of village apparatus, strengthening the role of the BPD, optimizing village deliberations, and applying public information disclosure through routine publication of the APBDes. This research is expected to serve as a reference for village governments and other stakeholders in improving village financial governance to realize effective, sustainable village development in accordance with the national legal framework.